The Evolution of Insurable Interest in Law and Practice: A Comparative Analysis of Marine and Life Insurance - Shuo Cao (Law and Economy, 2025)
Practically, it is widely believed that before the 18th century, the law was silent on the relationship between the insured and the subject matter insured. This results in the insured, who has nothing to do with the subject matter insured, gambling in the name of insurance for profit. It was common for the people who seemingly did not have any interests in the property likes of ship or cargo to try to obtain the proceeds of insurance by way of the insurance. In life insurance, it was even possible for people to insure the lives of public high-profile figures. If they succeed, they can make a lot of money. If it fails, it’s just a loss of premium. Such behavior violates the original purpose of insurance contracts, which is to transfer risk. This article discusses the position of insurable interest in marine insurance and life insurance. Comparing and analyzing related cases and the classification theory of insurable interest demonstrates the importance of adopting a more dynamic and open definition of insurable interest to the insurance market.